Pengaruh Program Muhadharah Terhadap Kelancaran Berbahasa Arab Santriwati Pondok Pesantren Manbaul Hidayah - Nadira Ulfa Hasibuan; Ali Imran Sinaga (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was conducted to find out how much influence Muhadharah extracurriculars have on the Arabic language fluency of female students at the Manbaul Hidayah Bunut West Islamic Boarding School. This research uses associative quantitative methods with data collection techniques in the form of observation, documentation and tests. Then the data obtained will be expressed in the form of diagrams or statistics. With this program, it is hoped that muhadharah will have a big influence on the female students' fluency in Arabic and can also increase the students' sense of self-confidence.